ANALISIS KAPASITAS WCDMA UTRA PADA JARINGAN SELULAR 3G - Subali (NIM 23299031), Eddy
Abstract : WCDMA UTRA is a direct sequence CDMA technology that uses chip rate 3.84 Mcps. This 3G system was proposed by European standarization body,ETSI, as a evolution step of 2G GSM and as a candidate which has fullfilled of ITU IMT-2000 recommendation. Because of 3G WCDMA system technology is different with 2G system, TDMA, it must be anticipated of its implementation. This thesis is a research about charecteristic of WCDMA, as a radio access interface and wanted to know its performance, such as covarage and system capacity on determined quality target that influenced by multi user interferences. Also, carried out of sectorization methode for improvement of capacity per site and choosing the design parameter of beamwidth and down tilt antenna in order to maximize of system capacity. Examination of this research, carried out on system level simulation. Two scenarios have been done on services that are speech 12.2 Kbps and data 64 Kbps, 144 Kbps, 384 Kbps. On the beginning of the research carried out scenario 1 : Model of multicell network that the centre of hexagonal cell is as a observation cell and influence of others cell interferences is represented by interference factor i that is ratio between others cell interferences and own cell interference (observation cell interference). On the further research step carried out scenario 2 : sytem level simulation that uses network model that are single cell Omni Antenna, configuration of 7 sites Omni Antenna, single site 3 Sectors Antenna (3 cells) and configuration of 7 sites 3 sectors antenna (21 cells) Simulation results shown that performance of WCDMA for capacity and coverage on determined quality target mostly influenced by multi user interferences. Improvement of system capacity could be done by sectorization and accurately choosing of design parameter of beamwidth and down tilt of antenna.